Self‐Polarized ZrO2/Poly(vinylidene fluoride‐co‐hexafluoropropylene) Nanocomposite‐Based Piezoelectric Nanogenerator and Single‐Electrode Triboelectric Nanogenerator for Sustainable Energy Harvesting from Human Movements. Issue 9 (9th March 2021) - Saikh, Md. Minarul; Hoque, Nur Amin; Biswas, Prosenjit; Rahman, Wahida; Das, Namrata; Das, Sukhen; Thakur, Pradip
Abstract : Piezoelectric nanogenerators (PENGs) have been emerged as one of the most promising approach for harvesting energy from the movement of living system for low‐power electronic devices. Herein, a simple PENG and single‐electrode triboelectric nanogenerator (STENG) are reported that execute tremendous output performance. In zirconium oxide (ZrO2 )/poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) nanocomposite polymer, ZrO2 acts as the nucleating agents for electroactive polymorph nucleation and also enhances the dielectric constant (≈23). Compared with previously reported PVDF‐HFP‐assisted prototype nanogenerators, this developed PENG exhibits excellent piezoelectric energy‐harvesting performance with very high power density, high energy conversion efficiency and high durability. The PENG exhibits a large value of open‐circuit voltage ≈120 V and short‐circuit current ≈1.95 μA under periodic finger imparting with high power density ≈7091 μW cm −3 . Fabricated flexible PENG is capable to instantaneously light up commercially available 55 number of blue light emitting diode connected in parallel connection through bridge rectifier. High capacitor charging performance is also observed, such as 2.2 μF capacitor charged up to 3.5 V, in just 17 s time interval. Single‐electrode‐based TENG fabricated by this composite film also shows remarkable output voltage ≈7 V under finger touch. Abstract : One of the most promising approaches for harvesting energy from the movement of living system for low‐power electronic devices is developed by fabricating two simple nanogenerators. Piezoelectric nanogenerator exhibits a voltage ≈120 V with current ≈1.95 μA under periodic finger imparting.